Terrorism today the past, the players, the future - Spindlove, Jeremy R (Pearson, 2013)
Taking an unbiased approach, Terrorism Today offers a lens into the history and status of terrorism around the world. Written with a global perspective, it addresses different regions of the world and the terrorist groups in each region. The text examines terrorist events and groups, analyzes responses to terrorism and the resulting changes in terrorist strategies, and steps through each continent mapping out current and future trends. The text's fifteen chapters build from historical backgrounds to predictions about terrorism in the twenty-first century.